Factors Associated with Poor Asthma Control among Sudanese Patients Attending Atbara Teaching Hospital in Sudan - Hadeel Kareem Aladdin; Sufian Khalid Mohammed Noor; Amro Mohamed Fagir Farah; Sara Elamin Bushara (Sudan Journal of Medical Sciences)
Objective: To identify factors associated with poor bronchial asthma control in patients attending Atbara Teaching Hospital, Sudan, in 2020. Methods: This was an analytical, descriptive, cross-sectional hospital-based study conducted at the Atbara Teaching Hospital in River Nile State, Sudan, between February and June 2020. All patients diagnosed with bronchial asthma who were attending any hospital department were included. Results: In total, 292 patients were enrolled, 51.4% were aged 18–45 years and 51.4% were female. The most frequent complaints were an audible wheeze and shortness of breath (approximately 93%), and 49% had been diagnosed with asthma >10 years previously. Of the patients, 42% were admitted 1 to 3 times and 47.3% were admitted to the intensive care unit (ICU). Hospital admission was associated with improper inhaler use (P = 0.003), the presence of triggers at home or work (P = 0.003), and passive smoking (P = 0.016). ICU admission was associated with female sex (P = 0.039) and the presence of triggers at home or work (P = 0.026). Conclusion: Asthma is a major problem in Atbara City. Improper inhaler use, the presence of triggers at home or work, and passive smoking were significantly associated with hospital admission. Female sex and the presence of triggers at home or work were significantly associated with ICU admission.